2018
DOI: 10.1128/jvi.00971-18
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Loss of APOBEC3H Activity during Primate Evolution

Abstract: Genes in the family encode cytidine deaminases that provide a barrier against viral infection and retrotransposition. Of all genes in humans, () is the most polymorphic: some haplotypes encode stable and active A3H proteins, while others are unstable and poorly antiviral. Such variation in human A3H affects interactions with the lentiviral antagonist Vif, which counteracts A3H via proteasomal degradation. In order to broaden our understanding of A3H-Vif interactions, as well as its evolution in Old World monke… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
3

Relationship

5
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…The evolution of the APOBEC3 locus is tightly linked to viral infections via a different arms race [ 63 , 64 ]. The structure and synteny in the APOBEC3 locus and the protein repertoire therein encoded are extremely lineage-specific (see for instance [ 65 , 66 ] for Chiroptera or [ 67 , 68 ] for Primates). It is thus important to note that the mutagenic role of host APOBEC3 enzymes acting onto viral genomes and exerting strong evolutionary pressures in a particular virus–host interaction may fuel viral adaptations, which facilitate viral transmission and colonisation of novel host species, as suggested for lentiviruses infecting Primates [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…The evolution of the APOBEC3 locus is tightly linked to viral infections via a different arms race [ 63 , 64 ]. The structure and synteny in the APOBEC3 locus and the protein repertoire therein encoded are extremely lineage-specific (see for instance [ 65 , 66 ] for Chiroptera or [ 67 , 68 ] for Primates). It is thus important to note that the mutagenic role of host APOBEC3 enzymes acting onto viral genomes and exerting strong evolutionary pressures in a particular virus–host interaction may fuel viral adaptations, which facilitate viral transmission and colonisation of novel host species, as suggested for lentiviruses infecting Primates [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the loss of A3H activity is not unique to humans, as an evolutionary analysis of A3H in Old World monkeys found that A3H activity has been lost in multiple primate species [43]. Moreover, several residues in the putative RNA binding region of Loop 1 were found to influence the antiviral potency of African green monkey and patas monkey A3H, providing further evidence that mutations introduced in this loop are a recurrent evolutionary mechanism that results in a loss of function [43]. It is unknown why these loss-of-function mutations of A3H arise and become fixed in multiple primate species despite the established importance of this restriction factor in the control of retroviruses.…”
Section: Discussionmentioning
confidence: 99%
“…The following day, cells were transfected with 600 ng provirus (HIV-1ΔVifΔEnvLuc2, unless otherwise noted), 100 ng L-VSV-G (vesicular stomatitis virus G), and 400 ng pcDNA4/TO.A3.3XFLAG or pcDNA4/TOPO empty vector unless otherwise indicated. At 72 h later, virus was harvested and normalized for virion production using an RT-qPCR assay, as described previously (41,42). A volume of virus equivalent to 2,000 mU/ml of reverse transcriptase was used for infection of SUPT1 cells.…”
Section: Methodsmentioning
confidence: 99%